Body mass index and all‐cause mortality in patients with hypertension. (14th July 2015) - Xu, Wenxin; Shubina, Maria; Goldberg, Saveli I.; Turchin, Alexander
Abstract : Objective: To characterize the relationship between body mass index (BMI) and all‐cause mortality among adults with hypertension. Methods: We conducted a retrospective cohort study of adults with hypertension from The Health Improvement Network primary care research database in the United Kingdom. Mortality rates within each BMI category were compared after adjustment for age, sex, pre existing medical conditions, smoking, alcohol use, and socioeconomic status. Results: During a median follow‐up period of 8.0 years, 34, 354 deaths occurred (8.8%) among the 388, 724 study patients. In multivariable analysis that included interaction terms between smoking, heavy alcohol use, preexisting cardiovascular disease and chronic obstructive pulmonary disease (COPD), and BMI category to account for these conditions' association with increased mortality at lower BMI levels, a U‐shaped relationship was observed between BMI and mortality, with no difference in mortality in overweight (25.0–29.9 kg/m 2 ) versus normal (18.5–24.9 kg/m 2 ) BMI (risk ratio 1.00, 95% confidence interval 0.95 to 1.04, P  = 0.80). In multivariable analysis that used narrower BMI categories, lowest mortality was observed between BMI of 23.0 and 26.9 kg/m 2 . Conclusions: Patients with hypertension who have no history of smoking, heavy alcohol use, cardiovascular disease, or COPD have lowest mortality between BMI of 23.0 and 26.9 kg/m 2 .